Soil Quality Analysis and Land Management Direction on Dry Land Areas in Tejakula and Buleleng Districts, Indonesia - Apriadi, Putu Agung; Trigunasih, Ni Made; Mega, I Made (Agro Bali : Agricultural Journal, 2025)
Declining agricultural yields on drylands in Tejakula Subdistrict are largely attributed to poor soil management practices, highlighting the urgent need for comprehensive soil quality assessment. This study aims to evaluate soil quality, identify limiting factors, and map the spatial distribution of soil quality to guide appropriate land management strategies. The research was conducted from January to June 2024 across twelve sampling points in ten villages using a purposive sampling technique. Both disturbed and undisturbed soil samples were analyzed for physical, chemical, and biological indicators, including bulk density, porosity, soil texture, pH, C-organic, CEC, nutrients (N, P, K), and microbial biomass carbon (C-biomass). The Minimum Data Set (MDS) method and a weighted additive model were applied to calculate the Soil Quality Index (IKT). The results showed that all sampling sites were categorized as having very good soil quality, with IKT scores ranging from 16.3 to 19.6. The study concludes that although soil quality is generally high, targeted management interventions such as organic amendments and balanced fertilization are still necessary to address site-specific limiting factors and ensure land productivity.